2002
DOI: 10.1007/s005350200080
|View full text |Cite
|
Sign up to set email alerts
|

Severe manifestation of acute hepatitis A recently found in Gunma, Japan

Abstract: Clinical data and manifestations were more severe in the recent outbreak than in the past outbreak of acute hepatitis A. It is important to be aware of hepatitis A virus infection and to take into account the available vaccination against hepatitis A virus in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It is reported that age ≥40 years (OR 6.91, p = 0.002), hepatitis B surface antigen positivity (OR 5.02, p = 0.049), and peak total bilirubin (OR 1.11, p = 0.001) are significant risk factors for ALF. 97 Kanda et al 98 also reported that two of the three patients with fulminant hepatitis A between 1998 and 1999 in Gunma Prefecture were over 40 years-of-age. The outcomes of patients with ALF or LOHF caused by HAV infection have recently worsened, mainly because of an increase in underlying metabolic diseases as a consequence of aging, 96 and multivariate analysis revealed that patient age and disease type are significantly and independently associated with the outcome.…”
Section: Age Over 40 Yearsmentioning
confidence: 96%
See 2 more Smart Citations
“…It is reported that age ≥40 years (OR 6.91, p = 0.002), hepatitis B surface antigen positivity (OR 5.02, p = 0.049), and peak total bilirubin (OR 1.11, p = 0.001) are significant risk factors for ALF. 97 Kanda et al 98 also reported that two of the three patients with fulminant hepatitis A between 1998 and 1999 in Gunma Prefecture were over 40 years-of-age. The outcomes of patients with ALF or LOHF caused by HAV infection have recently worsened, mainly because of an increase in underlying metabolic diseases as a consequence of aging, 96 and multivariate analysis revealed that patient age and disease type are significantly and independently associated with the outcome.…”
Section: Age Over 40 Yearsmentioning
confidence: 96%
“…It is reported that age ≥40 years (OR 6.91, p = 0.002), hepatitis B surface antigen positivity (OR 5.02, p = 0.049), and peak total bilirubin (OR 1.11, p = 0.001) are significant risk factors for ALF 97 . Kanda et al 98 . also reported that two of the three patients with fulminant hepatitis A between 1998 and 1999 in Gunma Prefecture were over 40 years‐of‐age.…”
Section: Consensus Statements and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only few persons are infected in early childhood, and the majority of adults thus remain susceptible to infection, which may lead to the occurrence of outbreaks of hepatitis A among the general population. The fatality rate in HAV infections is lower than 0·1%, although recent HAV outbreaks tend to be more severe (Kanda et al. 2002), e.g.…”
Section: Introductionmentioning
confidence: 99%